Does Gleason score of positive surgical margin after radical prostatectomy affect biochemical recurrence and oncological outcomes? Protocol for systematic review. Issue 3 (24th March 2020) - John, Athul; O'Callaghan, Michael; Catterwell, Rick; Selth, Luke
Abstract : Introduction: Positive surgical margins (PSM) in cancer patients are commonly associated with worse prognosis and a higher risk of secondary treatment. However, the relevance of this parameter in prostate cancer patients undergoing radical prostatectomy (RP) remains controversial, given the inconsistencies in its ability to predict biochemical recurrence (BCR) and oncological outcomes. Hence, further assessment of the utility of surgical margins for prostate cancer prognosis is required to predict these outcomes more accurately. Over the last decade, studies have used the Gleason score (GS) of positive margins to predict outcomes. Herein, the authors aim to conduct a systematic review investigating the role of GS of PSM after radical prostatectomy in predicting BCR and oncological outcomes. Methods and analysis: We will perform a search using MEDLINE, EMBASE, SCOPUS and COCHRANE databases. The review will be reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. We will screen titles and abstracts to select articles appropriate for full-text review. Studies discussing GS of PSM after RP will be included. Given the change in reporting of GS, only articles from 2005 to 2019 will be included. The quality of the studies chosen will be assessed using the Newcastle Ottawa tool for non-randomised and Cochrane risk of bias for randomised control studies. We will adopt the grading of recommendations, assessment, development and evaluation framework to comment on quality of cumulative evidence. The primary outcome measure will be time to BCR. Secondary outcome measures include secondary treatment, disease-specific survival, disease progression-free and overall mortality at follow-up period. We aim to perform a meta-analysis if the level of heterogeneity is acceptable (I 2 <50%). Ethics and dissemination: The review does not require ethics approval as it is a review of published literature. The findings of the review will be submitted for peer-reviewed publications and presented at scientific meetings. PROSPERO registration number: CRD42019131800.